Use of Vacuum-suction in Depressed Skull Fractures – Case Report and Technical Nuances of Nonoperative Treatment - Rodrigo Moreira Faleiro (Thieme Revinter Publicações Ltda., 2021)
Up to 20% of victims from skull fractures are represented by the pediatric population, and 50% of these lesions are depressed skull fractures. The treatment is multimodal in nature, ranging from conservative treatment to open surgical repair. The last one is associated, although in a small proportion, to complications, such as infections, hematomas and even death, besides the risks of the anesthetic procedure itself. The authors of the present article present a case report of the successful treatment of a depressed skull fracture in a newborn patient, using the vacuum-suction technique. The use of vacuum-suction may be beneficial for the pediatric patients, as it is a quick, non-invasive procedure, without the need for general anesthesia.